2009 IEEE Bucharest PowerTech 2009
DOI: 10.1109/ptc.2009.5282247
|View full text |Cite
|
Sign up to set email alerts
|

Local vs. wide-area undervoltage load shedding in the presence of induction motor loads

Abstract: Abstract-In the presence of induction motor loads, long-term voltage instability may end up in a sharp voltage decrease, which makes the tuning of undervoltage load shedding more delicate. This paper first investigates the ability of a purely distributed load shedding scheme, previously proposed by the authors, to cope with these situations. Owing to difficulties to reconcile dependability and security, an alternative wide-area protection is considered. The latter consists of generators sending overexcitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Tests reported in [9] have shown that the proposed widearea protection scheme performs very well against long-term voltage instability. Regarding the controller settings, tests carried out with V matter the voltage threshold value.…”
Section: B Identical Controllers Dealing With Long-term Instabilitymentioning
confidence: 95%
See 4 more Smart Citations
“…Tests reported in [9] have shown that the proposed widearea protection scheme performs very well against long-term voltage instability. Regarding the controller settings, tests carried out with V matter the voltage threshold value.…”
Section: B Identical Controllers Dealing With Long-term Instabilitymentioning
confidence: 95%
“…In the results presented so far (and in [9]) only nonmotor loads were curtailed. In principle, this leads to a more severe situation since the whole induction motor load remains connected to the system.…”
Section: B Identical Controllers Dealing With Long-term Instabilitymentioning
confidence: 99%
See 3 more Smart Citations